Ultrastructure and nuclear architecture of telomeric chromatin revealed by correlative light and electron microscopy - Hübner, Barbara (2022)
Telomeres, the ends of linear chromosomes, are composed of repetitive DNA sequences, histones and a protein complex called shelterin. How DNA is packaged at telomeres is an outstanding question in the field with significant implications for human health and disease. Here, we studied the architecture of telomeres and their spatial association with other chromatin domains in different cell types using correlative light and electron microscopy. To this end, the shelterin protein TRF1 or TRF2 was fused in tandem to eGFP and the peroxidase APEX2, which provided a selective and electron-dense label to interrogate telomere organization by transmission electron microscopy, electron tomography and scanning electron microscopy. Together, our work reveals, for the first time, ultrastructural insight into telomere architecture. We show that telomeres are composed of a dense and highly compacted mesh of chromatin fibres. In addition, we identify marked differences in telomere size, shape and chromatin compaction between cancer and non-cancer cells and show that telomeres are in direct contact with other heterochromatin regions. Our work resolves the internal architecture of telomeres with unprecedented resolution and advances our understanding of how telomeres are organized in situ.